2007
DOI: 10.1093/ndt/gfm588
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and ferritin levels in haemodialysis patients

Abstract: HD patients are in a higher oxidative state, which results in the reduction of total anti-oxidant capacity and also have an increased inflammation status. We could not find a relationship between ferritin level and OS markers in HD patients receiving erythropoietin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 30 publications
4
20
1
Order By: Relevance
“…In this study, we investigated the relationship between serum concentrations of CRP with plasma ferritin and did not found any association between them. These results conformed to Senol study (13).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we investigated the relationship between serum concentrations of CRP with plasma ferritin and did not found any association between them. These results conformed to Senol study (13).…”
Section: Discussionsupporting
confidence: 91%
“…Systemic inflammation is a common disorder in patients with CKD, which results from an increase in the production of oxidative stress-free radicals and a reduction in the capacity of antioxidants (13). It exacerbates with the deterioration of kidney function and hemodialysis inception (14).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased TAO capacity is consistent with numerous previous studies, which have shown that CRF and hemodialysis are contributing factors to oxidative stress (4,13,(32)(33)(34)(35). Previous work has demonstrated that levels of iron storage (serum ferritin) rise in HD patients (36). Increased iron content in circulation and tissues contributes to the generation of free radicals through the Fenton reaction.…”
Section: Discussionsupporting
confidence: 89%
“…High-dose Epo and elevated SUA were considered [14] to be aggravating factors for the prognosis of heart failure hemodialysis (HD) patients. Increased oxidative stress (OS) and inflammation but similar SUA were found [15] in maintenance HD patients receiving Epo compared with healthy control subjects. Nephrectomy increased [16] the SUA variably but did not change the Epo levels.…”
Section: Discussionmentioning
confidence: 75%